Comparison of dynamic visual acuity between water polo players and sedentary students - Quevedo-Junyent, L.; Aznar-Casanova, J. A.; Merindano-Encina, D.; Cardona, G.; Solé-Forto, J. (Research Quarterly for Exercise and Sport, 2011)
In this study, we examined differences in dynamic visual acuity between elite and subelite water polo players and sedentary students. To measure dynamic visual acuity binocularly, we asked participants to indicate the orientation of a broken ring, similar to the Landolt C, which increased in size as it moved across a computer screen. Two different speeds, three possible trajectories, and two different levels of contrast were evaluated. There were statistically significant differences between elite players and sedentary students for each combination of speed, contrast, and trajectory. Elite players achieved better dynamic visual acuity scores, and results also improved for some combinations of speed, contrast, and trajectory. Comparison between elite and subelite groups failed to reveal any